2015
DOI: 10.1002/mabi.201500131
|View full text |Cite
|
Sign up to set email alerts
|

POxylated Polyurea Dendrimers: Smart Core-Shell Vectors with IC50Lowering Capacity

Abstract: The design and preparation of highly efficient drug delivery platforms using green methodologies is at the forefront of nanotherapeutics research. POxylated polyurea dendrimers are efficiently synthesized using a supercritical-assisted polymerization in carbon dioxide. These fluorescent, pH-responsive and water-soluble core-shell smart nanocarriers show low toxicity in terms of cell viability and absence of glutathione depletion, two of the major side effect limitations of current vectors. The materials are al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 32 publications
2
27
0
1
Order By: Relevance
“…Figure 4 shows both the emission and excitation spectra of POxylated nanoparticles. The representative bands of POx-SH are maintained after particle grafting (λ exc = 300; λ emm = 384 nm) [26,27,42]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 4 shows both the emission and excitation spectra of POxylated nanoparticles. The representative bands of POx-SH are maintained after particle grafting (λ exc = 300; λ emm = 384 nm) [26,27,42]. …”
Section: Resultsmentioning
confidence: 99%
“…POXylation (grafting with oligo(2-ethyl-oxazolines), a similar strategy to PEGylation, currently under investigation to circumvent PEG hepatoxicity issues, has also been employed. Besides the ability to protect nanoparticles, POXylation also add fluorescent capabilities to the nanoparticles enabling an in vitro real time analysis of particles’ course within cell environments [26,27,28]. However, nanoparticles are not in a suitable size for deep lung deposition, as they can be easily exhaled or muccociliary cleared out [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This transformation was used to detect urea in urine by a phosphorescence sensor based on manganese doped zinc sulfide QDs . Polyureas are an important class of polymers, with applications in many fields, particularly, emergent polyurea dendrimers and their branched and hyperbranched counterparts . In this work, we investigated the molecular weight determination by enzymatic degradation using polyurea dendrimers as a case study, but linear and crosslinked polymers are envisaged to be suitable materials to investigate using this methodology.…”
Section: Overview Of Techniques and Detection Methods For Determinatimentioning
confidence: 99%
“…We also demonstrated that polyurea dendrimer nanoparticles POxylated using hydrophilic oligo‐oxazolines triggered a 100‐fold reduction in the median inhibitory concentration (IC 50 ) value of PTX relative to what was found in the free drug. This strategy was extended to the chemotherapeutic nano‐in‐micro dry powder formulations (DPFs) designed in this work . The synergies between nano‐ and microparticles ensure a quick delivery to the lung and enhance drug accumulation in neoplastic cells, which allow for: a faster response to the drug, a reduction in drug dosage, and consequently, a decrease in the number of undesired side effects.…”
Section: Introductionmentioning
confidence: 99%